Evaluating SCUBE-1 as Predictive Biomarker for Hypertension-Mediated Organ Damage: A Comparative Study - Betül Ayça Yamak; Mustafa Candemir; Emrullah Kızıltunç; Hüseyin Baran Özdemir; Özlem Gülbahar; Asife Şahinarslan (Reviews in Cardiovascular Medicine)
Background: Hypertension-mediated organ damage (HMOD) is a critical complication of hypertension that can present with cardiac, retinal, and renal manifestations and affect patient outcomes. Serum signal peptide, CUB (complement C1r/C1s, Uegf, and Bmp1) domain, and epidermal growth factor-like domain-containing protein 1 (SCUBE-1), a novel biomarker implicated in vascular pathology, shows promise for detecting HMOD. This study aims to explore the relation between SCUBE-1 levels and HMOD in hypertensive patients. Methods: This cross-sectional study included 115 participants, comprising 79 hypertensive patients and 36 healthy controls. The hypertensive patients were divided into two groups based on HMOD presence. SCUBE-1 levels were measured to evaluate their diagnostic utility in detecting HMOD. Results: Hypertensive patients exhibited significantly higher SCUBE-1 levels than controls (160.70 ng/mL vs. 75.64 ng/mL, p < 0.001). Among these patients, those with HMOD (cardiac, retinal, and renal) displayed even higher SCUBE-1 levels (311.27 ng/mL, range 137.86–460 ng/mL) compared to those without HMOD (142.53 ng/mL, range 110.56–178.19 ng/mL). Receiver operating characteristic curve analysis indicated that SCUBE-1 levels have significant diagnostic potential for differentiating between hypertensive patients with and without HMOD with area under the curve values of 0.722 for cardiac, 0.761 for retinal, and 0.707 for renal damage. Conclusions: Our study has revealed that SCUBE-1 levels are significantly elevated in hypertensive patients, particularly those with HMOD. The findings support the potential of SCUBE-1 as a valuable biomarker for predicting organ damage in hypertensive patients.